Modelagem generalizada do problema de planejamento da expansão de sistemas de transmissão - Nascimento, Edgar [UNESP] (2014)
In this work and in order to solve the long-term transmission expansion planning problems, a novel mathematical model which is based on a change in the concept of expanding a transmission system is presented. In traditional transmission system expansion planning, only the additions of candidate lines are considered. In this work, a new concept of transmission system expansion planning is to find a new solution for the base topology where all the lines are temporarily disconnected and the implementation of these lines are reconsidered when they may return to their previous position. Therefore, the lines of the base topology will not be reconnected if they prevent the system performance. Afterwards a new problem is solved to find the future plan of the electrical system network with the addition of new candidate lines in the modified base topology. In order to find a more efficient plan for the future network, the proposed methodology is implemented using a Modeling Language for Mathematical Programming (AMPL) and solved using the commercial solver of CPLEX. In order to validate the proposed approach and make some comparison with the method in the literature, three test systems are conducted such as: the 24-Bus IEEE test system with 41 candidate lines, a practical case studies of 46-Bus South Brazilian system with 79 candidate lines, and the 93-Bus Colombian system with 155 candidates. For large-scale systems, in order to facilitate the implementation of the mathematical model, a strategy to reduce the search space of the buses in which the generation or demand has been presented. In the transmission expansion planning problems, usually we face with a mixed integer non-linear programming problem (MINLP) using the DC model, which make it impossible to use the linear solver of CPLEX. The strategy to overcome this problem is using the disjunctive linear model, which is a DC linear equivalent model. The ...